PENENTUAN KONDISI PROSES PRODUKSI SURFAKTAN MES UNTUK APLIKASI EOR PADA BATUAN KARBONAT - Mira Rivai; Tun Tedja Irawadi; Ani Suryani; Dwi Setyaningsih (Agroindustrial Technology, University of Trunojoyo Madura, 2011)
Surfactant injection is one of the ways to lessen oil remains left in reservoir. This is done by injecting an active surface substance into reservoir until the tension of water-oil interface can be degraded. Reducing interfacial tension results in a reduced capillary pressure on pore stricture area of reservoir rocks until the oil caught in the pores can be pushed and produced. In order to make this process function optimally, an appropriate surfactant that fits the condition and formation of water and reservoir is needed. This study was conducted to get the best time of sulfonation process for producing MES surfactant with lower interfacial tension for EOR application at carbonate rock and to determine purification process of MES surfactant. Results showed that the best time of sulphonation to produce MES surfactant was from the third hour to the fourth hour. The selected purification process was conducted without methanol addition.